Women empowerment through micro-enterprises: An empirical Analysis of Kudumbashree units in Kerala - Ebrahim Kunju Sulaiman (Journal of Rural and Industrial Development, 2014)
Micro-enterprises foster the economic status of women as an effective mean to eradicate poverty. The income generating activities under individual and group initiatives to meet the livelihoods of the poor women are massively promoted under the schemes of Kudumbashree programmes in the state of Kerala. The study critically analyses the impact of micro-enterprises units run by the Kudumbashree programme in poverty eradication process and to compare the economic status of entrepreneurs before and after their membership in the enterprise. The study was conducted with the help of structured interview schedule administered to the 100 sample Kudumbashree micro-enterprise units in the state of Kerala. The analysis shows that the income level of the members of the units have a gradual progress after they become a member of the units.